Taxonomy of the bacterial strain bna5 isolated from ddt contaminated soil by analysing the nucleotide sequence of the 16s-rRNA gene - Minh, Nghiem Ngoc; Ngoc Mai, Cung Thi; Cam Ha, Dang Thi (Academia Journal of Biology, 2014)
The bacterial strain BNA5 was isolated from the DDT contaminated soil of heavy polluted sites. Belonging to positive gram bacteria, this strain had round and smooth colony with 2-5 mm diameter. The cell morphology of the strain BNA5 observed under the Scaning Electron Microscopy (SEM) showed that it was a short rod with 1.80-1.87 mm in length and 0.27-0.53 mm in wide. In this paper, the nucleotide sequence of the 16S rRNA gene had been used for taxonomy of the strain BNA5. Results of the amplification of the nucleotide sequence with the primers 314F/907R indicated that the strain BNA5 had high homology with the species of the genus Bacillus and was close to the Bacillus megaterium strain (DQ267829) and the strain Bacillus sp. R-16769 (AJ748259) at 99.83%. Based on the morphology and the 16S rRNA gene nucleotide sequence this strain was classified in the genus Bacillus and named Bacillus sp. BNA5. The nucleotide sequence of the 16S rRNA gene (550bp) was of the strain Bacillus sp. BNA5 deposited in the EMBL genbank database (with assession number AM398158)